Morrison R. Waite papers - Waite, Morrison R. (Morrison Remick), 1816-1888.
Correspondence, letterbooks, speeches, remarks, Supreme Court docket books, manuscripts and proofs of Circuit Court and Supreme Court opinions, Supreme Court assignments, obituary file, family papers, financial and legal records, printed matter, clippings, memorabilia, photographs, and other papers relating chiefly to Waite's service as U.S. Supreme Court chief justice. Correspondents include Benjamin Harris Brewster, Zachariah Chandler, Nathan Clifford, Roscoe Conkling, J.C. Bancroft Davis, Charles Devens, Frederick T. Frelinghuysen, William Greene, Hamilton Fish, John Marshall Harlan, Rutherford Birchard Hayes, Robert Todd Lincoln, Stanley Matthews, John G. Nicolay, Alexander Ramsey, and William T. Sherman.
Chief justice of the U.S. Supreme Court, jurist, and lawyer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brewster, Benjamin Harris, -- 1816-1888 -- Correspondence; Chandler, Zachariah, -- 1813-1879 -- Correspondence; Clifford, Nathan, -- 1803-1881 -- Correspondence; Conkling, Roscoe, -- 1829-1888 -- Correspondence; Davis, J. C. Bancroft -- 1822-1907 -- Correspondence; Devens, Charles, -- 1820-1891 -- Correspondence; Frelinghuysen, Frederick T. -- 1817-1885 -- Correspondence; Greene, William -- Correspondence; Fish, Hamilton, -- 1808-1893 -- Correspondence; Harlan, John Marshall, -- 1833-1911 -- Correspondence; Hayes, Rutherford Birchard, -- 1822-1893 -- Correspondence; Lincoln, Robert Todd, -- 1843-1926 -- Correspondence; Matthews, Stanley, -- 1824-1889 -- Correspondence; Nicolay, John G. -- 1832-1901 -- Correspondence; Ramsey, Alexander, -- 1815-1903 -- Correspondence; Sherman, William T. -- 1820-1891 -- Correspondence; Waite family; United States. -- Supreme Court; Circuit courts -- United States; Constitutional law -- United States; Courts -- United States; Judges -- United States; Judicial opinions -- United States; Law -- United States; Jurists; Lawyers